Performance Evaluation of Eco-Friendly Sucrose-BasedPlasticizer in Concrete (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Concrete is one of the most widely used construction materials in the world due toitsstrength, durability, and adaptability in various structural applications. However, theproduction and use of chemical admixtures in concrete may have environmental impacts, which has encouraged researchers to explore natural and eco-friendly alternatives. Organicsucrose, a naturally available carbohydrate, has the potential to act as a plasticizer andretarding admixture used in small quantities in concrete mixtures. The present studyinvestigates the effect of organic sucrose on the workability and mechanical propertiesofconcrete. Different concrete mixes were prepared by adding varying percentages of sucroserespect to the weight of cement. Laboratory tests such as slump test and compressivestrength test were conducted to evaluate the fresh and hardened properties of concrete. Theexperimental results indicate that the addition of a small amount of sucrose improves theworkability of concrete and slightly delays the setting time without significantly affectingitscompressive strength. The findings suggest that organic sucrose can be used as a sustainableand eco-friendly plasticizer in concrete, which may help in reducing dependency on syntheticchemical admixtures. This study highlights the potential of natural materials in developingenvironmentally responsible construction practices.